Arabic Idiomatic Translation Problems To Indonesian: Problematika Penerjemahan Idiomatik Arab Ke Indonesia - Muhammad Zairul Haq (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2022)
The idiomatic construction of Arabic has characteristics in which it does not only involve prepositions but also involves many things, such as historical logic that arises from cognitive-emotive to spirituality and the understanding of reality through idiomatic expressions. The purpose of this research is solely to review the problems of translating Arabic idioms into Indonesian. This research is descriptive qualitative. The object of the research is the construction of Arabic idiomatic languages and various problems of translating Arabic idioms to Indonesian which are often found in Arabic learning in universities, translation books, and relevant research results. The result showed that there have several fundamental things related to the emergence of cases of Arabic idiomatic translation into Indonesia are the influence of sama'i as a cultural product, inconsistencies in the meaning of prepositions, aspects of the context in the meaning of idioms, and the Arabic curriculum in Indonesia which is less accommodative to solving idiomatic translation cases. Konstruksi idiomatik bahasa Arab memiliki cirikhas yang di dalamnya tidak hanya melibatkan preposisi namun juga melibatkan banyak hal semisal dengan logika-historis yang muncul dari kesan kognitif-emotif hingga pengaruh spiritualitas dan pemahaman terhadap realitas secara benar melalui ungkapan-ungkapan idiomatik. Tujuan penelitian ini semata-mata untuk mengkaji problematika penerjemahan idiomatik bahasa Arab ke bahasa Indonesia. Penelitian ini bersifat deskriptif kualitatif. Objek penelitian adalah konstruksi idiomatik bahasa Arab dan berbagai permasalahan penerjemahan idiomatik Arab ke Indonesia yang banyak ditemui baik pada pembelajaran bahasa Arab di perguruan tinggi, buku terjemahan dan hasil penelitian yang relevan. Hasil penelitian menunjukkan ada beberapa hal mendasar terkait munculnya kasus penerjemahan idiomatik Arab ke Indonesia yaitu adanya pengaruh sama’I sebagai produk budaya, inkonsistensi pemaknaan preposisi, aspek konteks dalam pemaknaan idiom, dan kurikulum bahasa Arab di Indonesia yang kurang akomodatif terhadap penyelesaian kasus penerjemahan idiomatik.